Efektivitas Kinerja Pegawai Alih Daya Di PT PLN (PERSERO) Unit Pembangkitan Kelistrikan (UPK) Nagan Raya - Yeni Safitri; Sri Wahyu Handayani (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
This article aims to find out how the Effectiveness of Outsourced Employee Performance at PT PLN (Persero) UPK Nagan Raya, This study uses qualitative research methods. Data is collected through primary data and secondary data, researchers use performance theory from MitchellOutsourcing employee performance effectiveness, the opinion expressed by Mitchel himself in Sedarmayanti (2009: 51), that there are five aspects which include performance:, 1) quality of work, 2) punctuality in completing work, 3) initiative in completing work 4 ) capablecomplete work, 5) able to build cooperation with other parties (communication) Mitchell in Sedarmayanti (2009: 51), suggests that performance includes five aspects: 1) quality of work, 2) punctuality in completing work (promptness) , 3) inner initiativecomplete the work (initiative), 4) the ability to complete the work (capability), and 5) the ability to foster cooperation with other parties (communication). however, the effectiveness of the Outsourced Employee's performance at PT PLN (Persero) UPK Nagan Raya is still not optimal. research results that there isseveral obstacles in the field of quality of work, such as tasks given to employees that cannot be completed by employees within the allotted time, in the field of punctuality in completing work (promptness) there are still delays due to behaviorthe task is not in accordance with the intended purpose in the field.and there are still employees who do other work outside of their duties, in the area of ability to complete work (capability). Employee performance at PT PLN (Persero) UPK Nagan Raya is still In order to meet the standards, management is expected to be more consistent in returning results to employees who arecome late and go home inappropriately.Keywords: Effectiveness; Outsourced